Effect of Amphiphilic Compounds on Posthypertonic Lysis of Erythrocytes - Chabanenko, Olena; Yershova, Natalya; Shpakova, Natalia (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(3): 286